Foamed ceramic-based catalyst as well as preparation method and application thereof

By modifying the surface and sequentially coating ceramic slurries with varying solid contents, and doping zirconia and titanium dioxide, the method addresses the trade-off between porosity and compressive strength in foam ceramic catalysts, achieving high performance and stability.

CN119236922APending Publication Date: 2025-01-03SICHUAN SHUANGTIE TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411484489.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Existing foam ceramic-based catalysts face a trade-off between increased porosity, which enhances catalytic efficiency but reduces compressive strength, leading to breakage and decreased performance.

Method used

A method involving surface modifications and sequential coating of ceramic slurries with varying solid contents, combined with zirconia and titanium dioxide doping, to improve both porosity and compressive strength, and enhance photocatalytic performance.

Benefits of technology

The method results in foam ceramic-based catalysts with porosity ranging from 70 to 85% and compressive strength of 9 to 12 MPa, maintaining high photocatalytic activity and mechanical stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005098375700000091
    Figure BDA0005098375700000091
  • Figure BDA0005098375700000101
    Figure BDA0005098375700000101
Patent Text Reader

Abstract

The invention belongs to the technical field of photocatalytic materials, and provides a foamed ceramic-based catalyst as well as a preparation method and application thereof. The method comprises the following steps: S1, sequentially carrying out surface alkali treatment, surfactant modification and surface grafting modification on an organic foam template to obtain a modified foam template; s2, preparing a plurality of ceramic slurry with different solid contents, wherein the ceramic slurry comprises the following components: a binder, a rheological agent, a dispersant, a plasticizer, a zirconium oxide stabilizer, zirconium oxide, manganese dioxide, titanium dioxide, silicon dioxide and a solvent; s3, according to the slurry hanging sequence of the solid contents from high to low, ceramic slurry with different gradient solid contents is sequentially coated and hung on the surface of the modified foam template, drying and sintering are conducted, and the foamed ceramic-based catalyst is obtained. According to the invention, the surface of the organic foam template is modified, the components of the ceramic slurry are reasonably designed, and the ceramic slurry with gradient solid content is adopted for multiple times of slurry hanging, so that the porosity and compression strength of the foamed ceramic-based catalyst are simultaneously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of photocatalytic materials, and in particular relates to a foam ceramic-based catalyst and a preparation method and application thereof. Background Art

[0002] Foam ceramic-based catalysts are advanced composite materials that combine the porous structure of foam ceramic materials with catalytic activity. Foam ceramics are known for their high porosity, good mechanical strength, excellent thermal stability and chemical stability. When these properties are combined with specific catalytically active substances, foam ceramic-based catalysts are formed. This type of catalyst exhibits advantages such as high efficiency, stability and easy recycling in catalytic reactions, and is widely used in many fields such as environmental protection, energy conversion, and chemical industry.

[0003] The increase in porosity of foam ceramic-based catalysts has the advantages of improving catalytic efficiency, enhancing mass transfer performance and increasing the number of active sites. However, the increase in porosity means a decrease in compressive strength. The decrease in compressive strength will lead to easy breakage or deformation during use, thereby causing a rapid decrease in its catalytic performance. Chinese patent CN118079895A discloses a preparation method of a bismuth vanadate / aluminum oxide foam ceramic composite photocatalytic material, directly loading the catalytic material on the surface of the foam ceramic material, but the porosity and compressive strength of the existing commercial grade foam ceramic material are relatively low. Chinese patent CN 109382085 A discloses a rare earth mineral foam ceramic catalyst and its preparation method and application, using ceramic slurry and polyurethane foam template to prepare foam ceramics, but the hanging efficiency of the ceramic slurry is low, resulting in low compressive strength, which is not conducive to the long-term use of the foam ceramic catalyst. Therefore, based on the above description, it is urgent to develop a foam ceramic-based catalyst that can simultaneously increase the porosity of the catalyst and improve the compressive strength of the catalyst. Summary of the invention

[0004] In view of the above-mentioned deficiencies in the prior art, the purpose of the present invention is to simultaneously improve the porosity and compressive strength of foam ceramic-based catalysts.

[0005] The present invention is achieved through the following technical solutions:

[0006] A method for preparing a foam ceramic-based catalyst comprises the following steps:

[0007] S1, sequentially subjecting the organic foam template to surface alkali treatment, surfactant modification and surface grafting modification to obtain a modified foam template;

[0008] S2. preparing a plurality of ceramic slurries with different solid contents, wherein the components of the ceramic slurry include a binder, a rheological agent, a dispersant, a plasticizer, a zirconia stabilizer, zirconia, manganese dioxide, titanium dioxide, silicon dioxide and a solvent;

[0009] S3. In the order of coating from high to low solid content, the ceramic slurries with gradient different solid contents are coated on the surface of the modified foam template respectively, and then dried and sintered to obtain a foam ceramic-based catalyst.

[0010] In order to improve the high temperature stability of zirconia ceramics and reduce the volume effect caused by phase change, the present invention adds a stabilizer to the zirconia ceramics. The stabilizer can reduce the lattice parameter of zirconia, reduce the lattice deformation and the generation of lattice cracks, thereby improving the stability and durability of zirconia. By adding manganese dioxide to the ceramic slurry, it can be used as a sintering aid and a precursor of the active component of the catalyst to promote the sintering process and improve the activity of the catalyst, and at the same time reduce the sintering temperature and save energy. By adding silicon dioxide, a crystal form conversion control agent, to the titanium dioxide precursor, the problem of crystal form conversion of nano titanium dioxide at high temperature is solved, so that after high temperature sintering, its crystal form is still anatase or anatase and rutile composite crystal form, maintaining a high photocatalytic performance.

[0011] The present invention adds zirconium oxide and titanium dioxide to the ceramic slurry at the same time, and the two act synergistically to improve the photocatalytic performance. 4+ ) is doped into the titanium dioxide lattice to form a Zr-O-Ti bond. The formation of this bond helps to change the band structure of titanium dioxide, making it have a stronger visible light absorption ability. At the same time, doping can also inhibit the recombination of photogenerated electrons and holes and improve the quantum efficiency. In addition, zirconium oxide and titanium dioxide act as electron acceptors and hole acceptors, respectively, forming an effective charge separation and transmission channel. This structure not only improves the separation efficiency of photogenerated carriers, but also prolongs the carrier lifetime, thereby enhancing the photocatalytic activity.

[0012] The present invention first uses a slurry with a high solid content for slurry coating, which can quickly form a thicker coating on the surface of the foam template and preliminarily fix the skeleton structure of the foam template. This coating can maintain good stability during the subsequent drying and sintering process, providing a solid foundation for the subsequent slurry coating operation. Then, a slurry with a medium solid content is used for slurry coating. This layer of slurry can penetrate into the tiny pores of the previous layer of coating, further optimizing the pore structure and pore size distribution. At the same time, since the medium solid content slurry has a certain fluidity, it can ensure the uniform distribution of the coating on the surface of the foam template. Finally, a slurry with a low solid content is used for slurry coating. This layer of slurry has fewer ceramic particles and more bubbles formed after the water evaporates, which can significantly increase the porosity of the foam ceramic-based catalyst. At the same time, since the low solid content slurry has good fluidity, it can further penetrate into the pores of the first two layers of coating to form a more complex three-dimensional network structure, which is beneficial to improving the distribution of the active components of the catalyst in the pores and the progress of the catalytic reaction.

[0013] Further, the surface grafting modification includes:

[0014] The surfactant-modified organic foam template is immersed in a polyacrylamide solution, and then ammonium persulfate is added and heated in a water bath; wherein,

[0015] The mass concentration of the polyacrylamide is 5 to 15%;

[0016] The mass concentration of the ammonium persulfate is 0.5-1.5%;

[0017] The water bath heating temperature is 40 to 60° C., and the water bath heating time is 2 to 6 hours.

[0018] Further, the surfactant modification includes:

[0019] The organic foam template after surface alkali treatment is immersed in a surfactant; wherein,

[0020] The soaking temperature is 40 to 60° C., and the soaking time is 1 to 3 hours;

[0021] The mass concentration of the surfactant is 5 to 15%;

[0022] The surfactant includes one or more of polyethyleneimine, sodium carboxymethylcellulose, polyethylene glycol and sodium dodecyl sulfate.

[0023] Further, the surface alkali treatment includes:

[0024] The organic foam template is immersed in a sodium hydroxide solution; wherein,

[0025] The mass concentration of the sodium hydroxide is 5 to 15%;

[0026] The soaking temperature is 40-60° C., and the soaking time is 4-6 hours.

[0027] Furthermore, the mass m1 of the binder, the mass m2 of the rheological agent, the mass m3 of the dispersant, the mass m4 of the plasticizer, the mass m5 of the zirconium oxide stabilizer, the mass m6 of the zirconium oxide, the mass m7 of the manganese dioxide, the mass m8 of the titanium dioxide and the mass m9 of the silicon dioxide satisfy the following relationship:

[0028] m1:m2:m3:m4:m5:m6:m7:m8:m9=(0.5~1.5):(2~4):(0.5~1.5):(0.5~1.5):(2~4):(20~40):(2~4):(5~15):(1~3).

[0029] Furthermore, the binder includes: one or more of polyvinyl alcohol, sodium carboxymethyl cellulose, polyethyleneimine, silica sol, aluminum phosphate and borate;

[0030] The rheological agent includes: one or more of carboxymethyl cellulose, hydroxyhexyl cellulose, bentonite and kaolin;

[0031] The dispersant includes: one or more of sodium polymetaphosphate, polyacrylamide, polyvinyl alcohol and polyvinyl ether;

[0032] The plasticizer includes: one or more of polyvinyl alcohol, polyvinyl ether, hydroxyethyl methyl cellulose, dioctyl phthalate and polyvinyl alcohol;

[0033] The zirconium oxide stabilizer includes one or more of calcium oxide, aluminum oxide and magnesium oxide.

[0034] Furthermore, the number of the ceramic slurries with gradient solid content is ≥ 3, including: ceramic slurry solid content of 75-85%, ceramic slurry solid content of 70-80%, ceramic slurry solid content of 65-75%, and ceramic slurry solid content of 60-70%.

[0035] Furthermore, the sintering temperature is 1100-1300° C., and the sintering time is 90-180 min.

[0036] The second object of the present invention is to provide a foam ceramic-based catalyst obtained by the preparation method of the foam ceramic-based catalyst described in any one of the above embodiments, wherein the foam ceramic-based catalyst satisfies at least one of the following properties: a porosity of 70 to 85% and a compressive strength of 9 to 12 MPa.

[0037] The third object of the present invention is to provide an application of the foam ceramic-based catalyst described in the above embodiment, wherein the foam ceramic-based catalyst is used for photocatalytic degradation of volatile organic compounds.

[0038] The beneficial effects of the present invention are:

[0039] (1) The surface of the organic foam template is made rough and uneven by alkali treatment, which increases the contact area with the surfactant and thus increases its loading capacity. A layer of obvious organic matter is coated on the surface of the organic foam template by surfactant modification, and the uneven coating of the organic matter increases the surface roughness of the organic foam template, which greatly improves the contact area and hydrophilicity of the polyurethane sponge. Hydrophilic groups such as carboxyl groups are directly introduced into the sponge by surface grafting modification, which effectively improves the hydrophilicity. The synergistic effect of surface alkali treatment, surfactant modification and surface grafting modification helps the water-based ceramic slurry to fully wet the polyurethane, thereby increasing the amount of slurry on the green body and the mechanical properties of the foam ceramic.

[0040] (2) The role of the binder in the ceramic slurry of the organic foam impregnation method is to improve the bonding ability of the slurry, so that the slurry can adhere firmly to the foam sponge skeleton, improve the strength of the green body after drying, and prevent the green body from collapsing due to the loss of the foam skeleton during sintering, so as to ensure that the foam ceramic obtained by the final sintering has a complete shape and sufficient mechanical strength. The organic foam impregnation method requires that the ceramic slurry has excellent fluidity to facilitate slurry hanging, and also has a certain thixotropy to ensure stability after slurry hanging, that is, the slurry is required to be in a solidified state when not subjected to external forces, and to return to a fluid state when subjected to external forces, and has the characteristics of flow. The fluidity of the slurry allows it to enter the interior of the foam sponge and be evenly mounted on the sponge skeleton, and squeeze out excess slurry under the action of external forces, while the solidified state when stationary allows the slurry to be firmly and evenly mounted on the skeleton. The dispersant can make the solid particles in the prepared ceramic slurry dispersed evenly and maintain the stability of the slurry. Adding a dispersant can effectively reduce the re-agglomeration of ceramic solid particles in the slurry, thereby increasing the solid content of the slurry. Plasticizers in slurry usually refer to chemical substances dissolved in the slurry, which are mainly used to adjust the fluidity and formability of the slurry.

[0041] (3) The coating sequence from high to low solid content can improve the porosity and compressive strength of the foam ceramic-based catalyst at the same time. By controlling the coating sequence and coating thickness of slurries with different solid contents, foam ceramic-based catalysts with excellent performance can be prepared. DETAILED DESCRIPTION

[0042] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0043] Example 1

[0044] This embodiment provides a method for preparing a foam ceramic-based catalyst, which may include the following steps:

[0045] S11. The polyurethane sponge is subjected to surface alkali treatment, surfactant modification and surface grafting modification in sequence to obtain a modified foam template; the surface alkali treatment uses a sodium hydroxide solution with a mass concentration of 10%, a temperature of 50°C, and a time of 2 hours; the surfactant modification uses sodium carboxymethyl cellulose with a mass concentration of 10%, the immersion temperature is 50°C, and the immersion time is 2 hours; the mass concentration of the surface grafted modified polyacrylamide is 10%, the mass concentration of ammonium persulfate is 1%, the water bath heating temperature is 50°C, and the water bath heating time is 4 hours;

[0046] S21. Mix a binder, a rheological agent, a dispersant, a plasticizer, a zirconia stabilizer, zirconia, manganese dioxide, titanium dioxide, silicon dioxide and a solvent to obtain ceramic slurries with gradient solid content; wherein the binder is CMC-Na, the rheological agent is bentonite, the dispersant is PAA-NH4, the plasticizer is DOP, the zirconia stabilizer is magnesium oxide, and the solvent is water, the mass of the binder is m1, the mass of the rheological agent is m2, the mass of the dispersant is m3, and the mass of the plasticizer is m 4. The mass m5 of zirconium oxide stabilizer, the mass m6 of zirconium oxide, the mass m7 of manganese dioxide, the mass m8 of titanium dioxide and the mass m9 of silicon dioxide satisfy the following relationship: m1:m2:m3:m4:m5:m6:m7:m8:m9=1:3:1:1:3:30:3:10:2. The gradient solid content includes: ceramic slurry solid content of 80%, ceramic slurry solid content of 75%, ceramic slurry solid content of 70%, and ceramic slurry solid content of 65%.

[0047] S31. Ceramic slurries with gradient solid contents are coated on the surface of the modified foam template in order of solid content from high to low, and dried at 60°C for 12h, and then sintered at 1200°C for 150min to obtain a foam ceramic-based catalyst.

[0048] Example 2

[0049] The difference between this embodiment and Embodiment 1 is that the mass m1 of the binder, the mass m2 of the rheological agent, the mass m3 of the dispersant, the mass m4 of the plasticizer, the mass m5 of the zirconium oxide stabilizer, the mass m6 of zirconium oxide, the mass m7 of manganese dioxide, the mass m8 of titanium dioxide and the mass m9 of silicon dioxide satisfy the following relationship: m1:m2:m3:m4:m5:m6:m7:m8:m9=1:3:1:1:3:40:3:10:2.

[0050] Example 3

[0051] The difference between this embodiment and embodiment 1 is that the mass m1 of the binder, the mass m2 of the rheological agent, the mass m3 of the dispersant, the mass m4 of the plasticizer, the mass m5 of the zirconium oxide stabilizer, the mass m6 of zirconium oxide, the mass m7 of manganese dioxide, the mass m8 of titanium dioxide and the mass m9 of silicon dioxide satisfy the following relationship: m1:m2:m3:m4:m5:m6:m7:m8:m9=1:3:1:1:3:20:3:10:2.

[0052] Example 4

[0053] The difference between this embodiment and embodiment 1 is that the sintering is performed at 1100° C. for 150 min.

[0054] Example 5

[0055] The difference between this embodiment and embodiment 1 is that the sintering is performed at 1300° C. for 150 min.

[0056] Example 6

[0057] The difference between this embodiment and embodiment 1 is that the gradient solid content includes: the ceramic slurry solid content is 80%, the ceramic slurry solid content is 75%, and the ceramic slurry solid content is 70%.

[0058] Comparative Example 1

[0059] The difference between this comparative example and Example 1 is that no surface grafting modification treatment is performed in step S11.

[0060] Comparative Example 2

[0061] The difference between this comparative example and Example 1 is that the mass m1 of the binder, the mass m2 of the rheological agent, the mass m3 of the dispersant, the mass m4 of the plasticizer, the mass m5 of the zirconium oxide stabilizer, the mass m6 of zirconium oxide, the mass m7 of manganese dioxide, the mass m8 of titanium dioxide and the mass m9 of silicon dioxide satisfy the following relationship: m1:m2:m3:m4:m5:m6:m7:m8:m9=1:3:1:1:3:40:0:10:2.

[0062] Comparative Example 3

[0063] The difference between this comparative example and Example 1 is that the mass m1 of the binder, the mass m2 of the rheological agent, the mass m3 of the dispersant, the mass m4 of the plasticizer, the mass m5 of the zirconium oxide stabilizer, the mass m6 of zirconium oxide, the mass m7 of manganese dioxide, the mass m8 of titanium dioxide and the mass m9 of silicon dioxide satisfy the following relationship: m1:m2:m3:m4:m5:m6:m7:m8:m9=1:3:1:1:3:50:5:0:0.

[0064] Comparative Example 4

[0065] The difference between this comparative example and Example 1 is that the mass m1 of the binder, the mass m2 of the rheological agent, the mass m3 of the dispersant, the mass m4 of the plasticizer, the mass m5 of the zirconium oxide stabilizer, the mass m6 of zirconium oxide, the mass m7 of manganese dioxide, the mass m8 of titanium dioxide and the mass m9 of silicon dioxide satisfy the following relationship: m1:m2:m3:m4:m5:m6:m7:m8:m9=1:3:1:1:3:40:3:12:0.

[0066] Comparative Example 5

[0067] The difference between this comparative example and Example 1 is that the gradient solid content includes: the ceramic slurry solid content is 80% and the ceramic slurry solid content is 75%.

[0068] Comparative Example 6

[0069] The difference between this comparative example and Example 1 is that the solid content of the ceramic slurry is 80%.

[0070] The porosity and compressive strength of the foamed ceramic-based catalysts obtained in the examples and comparative examples were tested, and the results are shown in Table 1. The porosity of the foamed ceramic-based catalysts was measured by gas adsorption method (the adsorption characteristics of gas on the surface of the material are used to measure the pore structure), and the compressive strength of the foamed ceramic-based catalysts was measured by GB / T 1964-1996 "Test Method for Compressive Strength of Porous Ceramics".

[0071] Table 1 Porosity and compressive strength of foam ceramic-based catalysts

[0072] Group Porosity, % Compression strength, Mpa Example 1 75 11.1 Example 2 77 10.8 Example 3 81 10.4 Example 4 78 10.9 Example 5 82 9.9 Example 6 83 10.1 Comparative Example 1 70 8.7 Comparative Example 2 75 9.1 Comparative Example 3 79 10 Comparative Example 4 81 9.7 Comparative Example 5 90 4.5 Comparative Example 6 95 0.35

[0073] The photocatalytic performance of the foam ceramic-based catalysts obtained in the examples and comparative examples was tested according to Japanese standard JIS R1701:2008 “Precision ceramics—Test method for air purification performance of photocatalyst materials”. The results are shown in Table 2.

[0074] Table 2 Photocatalytic performance of foam ceramic-based catalysts

[0075]

[0076]

[0077] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a foam ceramic-based catalyst, characterized in that: The steps include: S1, sequentially subjecting the organic foam template to surface alkali treatment, surfactant modification and surface grafting modification to obtain a modified foam template; S2. preparing a plurality of ceramic slurries with different solid contents, wherein the components of the ceramic slurry include a binder, a rheological agent, a dispersant, a plasticizer, a zirconia stabilizer, zirconia, manganese dioxide, titanium dioxide, silicon dioxide and a solvent; S3. In the order of the solid content from high to low, the ceramic slurries with different solid contents are coated on the surface of the modified foam template respectively, and then dried and sintered to obtain a foam ceramic-based catalyst.

2. The method for preparing a foam ceramic-based catalyst according to claim 1, characterized in that: The surface grafting modification comprises: The surfactant-modified organic foam template is immersed in a polyacrylamide solution, and then ammonium persulfate is added and heated in a water bath; wherein, The mass concentration of the polyacrylamide is 5 to 15%; The mass concentration of the ammonium persulfate is 0.5-1.5%; The water bath heating temperature is 40 to 60° C., and the water bath heating time is 2 to 6 hours.

3. The method for preparing a foam ceramic-based catalyst according to claim 2, characterized in that: The surfactant modification includes: The organic foam template after surface alkali treatment is immersed in a surfactant; wherein, The soaking temperature is 40 to 60° C., and the soaking time is 1 to 3 hours; The mass concentration of the surfactant is 5 to 15%; The surfactant includes one or more of polyethyleneimine, sodium carboxymethylcellulose, polyethylene glycol and sodium dodecyl sulfate.

4. The method for preparing a foam ceramic-based catalyst according to claim 3, characterized in that: The surface alkali treatment comprises: The organic foam template is immersed in a sodium hydroxide solution; wherein, The mass concentration of the sodium hydroxide is 5 to 15%; The soaking temperature is 40-60° C., and the soaking time is 4-6 hours.

5. The method for preparing a foam ceramic-based catalyst according to claim 1, characterized in that: The mass m1 of the binder, the mass m2 of the rheological agent, the mass m3 of the dispersant, the mass m4 of the plasticizer, the mass m5 of the zirconium oxide stabilizer, the mass m6 of the zirconium oxide, the mass m7 of the manganese dioxide, the mass m8 of the titanium dioxide and the mass m9 of the silicon dioxide satisfy the following relationship: m1:m2:m3:m4:m5:m6:m7:m8:m9=(0.5~1.5):(2~4):(0.5~1.5):(0.5~1.5):(2~4):(20~40):(2~4):(5~15):(1~3).

6. The method for preparing a foam ceramic-based catalyst according to claim 5, characterized in that: The binder includes: one or more of polyvinyl alcohol, sodium carboxymethyl cellulose, polyethyleneimine, silica sol, aluminum phosphate and borate; The rheological agent includes: one or more of carboxymethyl cellulose, hydroxyhexyl cellulose, bentonite and kaolin; The dispersant includes: one or more of sodium polymetaphosphate, polyacrylamide, polyvinyl alcohol and polyvinyl ether; The plasticizer includes: one or more of polyvinyl alcohol, polyvinyl ether, hydroxyethyl methyl cellulose, dioctyl phthalate and polyvinyl alcohol; The zirconium oxide stabilizer includes one or more of calcium oxide, aluminum oxide and magnesium oxide.

7. The method for preparing a foam ceramic-based catalyst according to claim 1, characterized in that: The number of the ceramic slurries with gradient solid content is ≥3, including: ceramic slurry solid content of 75-85%, ceramic slurry solid content of 70-80%, ceramic slurry solid content of 65-75%, and ceramic slurry solid content of 60-70%.

8. The method for preparing a foam ceramic-based catalyst according to claim 1, characterized in that: The sintering temperature is 1100-1300° C., and the sintering time is 90-180 minutes.

9. A foamed ceramic-based catalyst obtained by the method for preparing a foamed ceramic-based catalyst according to any one of claims 1 to 8, characterized in that: The foam ceramic-based catalyst meets at least one of the following properties: a porosity of 70 to 85% and a compression strength of 9 to 12 MPa.

10. Use of the foam ceramic-based catalyst according to claim 9, characterized in that: The foam ceramic-based catalyst is used for photocatalytic degradation of volatile organic matter.

Citation Information

Cited By

  • Dehydrogenation porous structure ceramic fire-retardant material and preparation method and application thereof

    CN120590154A